The Effective Training Management Model of Learning Guardian in BPPLSP Surabaya, Indonesia - Achmad Rasyad (LPPM UNY, 2013)
This study is aimed at finding out factors that determine the effectiveness of training processes factors that determine the effectiveness of training results. The study used an ex-post facto design. A total of 60 participants took part in the study. Datat analysis was done in percentages. The research finding shows that factors such as participants, trainers, training materials, and working environment play significant roles in the training process; factors such as participants, trainers, training materials and working environment affect the training result with the finding notes: (a) trainees' do not only significantly influence the training result through the training process, but they also have direct irifluence to the training result; (b) the instructors and training materials contribute the training result indirectly; and (c) working environment does not only significantly influence the training result through the training process, but it also gives direct irifluence to the training result.